Representasi Budaya Generasi Millenial Muslim (Studi Semiotika Vlog Taqi Malik Di Youtube) - Gan Gan Giantika; Marlinda Irwanti Poernomo; Hayu Lusianawati (Jurnal Komunikasi, 2022)
AbstractMillennials are a productive age that is considered as the determinant of the future direction in the nation's culture. The formulation of this research problem is how the Cultural Representation of Muslim Millennials (Vlog Taqi Malik Semiotics Study On YouTube) ?. The purpose of this study is to find out the Cultural Representation of Muslim Millennials (Vlog Taqi Malik Semiotics Study On YouTube). This research uses a paradigm of constructivism with a descriptive qualitative research approach and uses ferdinand de Saussure's semiotic analysis method. The results of this study showed from Taqi Malik vlog as many as 3 (three) episodes, namely episodes : Alasan Milih Dia Jadi Istri (Part 1), Hari Meminang Serell Thalib, dan Menjenguk Kai Basri Kondisi Beliau Sangat Memprihatinkan, using language and text as identities and these three videos represent the culture of muslim millennials in the form of Islamic content. With the paradigm approach of constructivism, more emphasis on language and text so as to construct a meaning composed of signifiers and signified until finally form a meaning or referent (external reality). Keywords : Cultural Representation, Muslim Millennials, Semiotics Ferdinand De Saussure